Binding technique on the ground in the study of the effects of man-caused accidents - Batiy, V.G.; Glebkin, S.I.; Kochnev, N.A.; Selyukova, V.V.; Prokhorets, S.I.; Fedorchenko, D.V.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2013)
The technique of determining the coordinates of the point of measuring device location during the researches in contaminated areas and near the radiation- and chemically-dangerous objects is proposed. It is shown the optimal way is the integrated usage of different methods: linear resection using laser range finders; tachymeters; GPS systems. Запропоновано методику визначення координат точки розмiщення вимiрювальної установки при проведеннi дослiдженьна забруднених територiях та поблизу радiацiйно- та хiмiчно небезпечних об’єктiв. Показано, що оптимальним є комплексне використання рiзних методiв: лiнiйної засiчки iз застосуванням лазерних далекомiрiв, тахеометрiв, системи GPS. Предложена методика определения координат точки размещения измерительной установки при проведении исследований на загрязненных территориях и вблизи радиационно- и химически опасных объектов. Показано, что оптимальным является комплексное использование разных методов: линейной засечки с применением лазерных дальномеров, тахеометров, системы GPS.